Exploring gender discrimination: A multi-trial field experiment in urban Ecuador - Wladimir Zanoni; Suzanne Duryea; Jorge Paredes (Inter-American Development Bank (IDB), 2024)
In this study, we investigate the extent and mechanisms of gender-based discrimination in urban Ecuador's hiring practices, a critical issue for understanding persistent gender disparities and informing policy. Using an artifactual field experiment with 392 recruiters evaluating observationally equivalent male and female job candidates, we uncover a significant preference for female candidates. Our results show that women were preferred by a margin of 15%, despite equivalent productivity assessments between genders. This suggests that hiring decisions are influenced by factors beyond assessed productivity differentials. We hypothesize that social norms advocating for gender equality significantly drive these preferences, and demonstrate that the preference for women aligns with the observed trend of narrowing the employment gender gap in survey data.
Keywords: J16; J71; C93; 330; Gender discrimination; Occupational segregation; Labor market; Stereotyping